Outcome in VLBW infants with surgical intestinal disorder at 18 months of corrected age. Issue 4 (6th May 2015) - Hayakawa, Masahiro; Taguchi, Tomoaki; Urushihara, Naoto; Yokoi, Akiko; Take, Hiroshi; Shiraishi, Jun; Fujinaga, Hideshi; Ohashi, Kensuke; Oshiro, Makoto; Kato, Yuichi; Ohfuji, Satoko; Okuyama, Hiroomi
Abstract Background Surgical intestinal disorders, such as necrotizing enterocolitis (NEC), focal intestinal perforation (FIP), and meconium‐related ileus (MRI), are serious morbidities in very low‐birthweight infants (VLBWI). The aim of this study was to compare the composite outcomes of death or neurodevelopmental impairment (NDI) in VLBWI with surgical intestinal disorders and assess independent risk factors for death and NDI at 18 months of corrected age. Methods A retrospective matched‐cohort study was conducted at 11 institutes. We included VLBWI who had undergone laparotomy for NEC, FIP, and MRI. Two control subjects were chosen for every surgical patient and matched for gestational age and birthweight to form the comparison group. Death and neurodevelopmental outcome at 18 months of corrected age were evaluated. Results The number of infants in the NEC, FIP, MRI, and control groups was 44, 47, 42, and 261, respectively. In‐hospital mortality was higher in infants with NEC and MRI relative to those in the control group (P < 0.001). The incidence rate for NDI at 18 months of corrected age was higher in infants with MRI relative to those in the control group (P = 0.021). On logistic regression analysis, low gestational age, male sex, small for gestational age, intraventricular hemorrhage, and MRI were associated with increased risk of death or NDI at 18 months of corrected age. Conclusions NEC and MRI were associated with in‐hospital mortality, and MRI was associated with NDI or death at 18 months of corrected age.